1989
DOI: 10.1002/jez.1402500212
|View full text |Cite
|
Sign up to set email alerts
|

Mating‐induced release of granules by the endocrine dorsal body cells of the snail Helisoma duryi (Mollusca)

Abstract: The hermaphrodite snail Helisoma duryi reproduces preferentially by cross-fertilization. Virgin and castrated snails lay an insignificant number of egg masses. The fine structure of its endocrine dorsal bodies (DB), which regulate reproduction, has been studied in reproductively inactive virgin and castrated snails and in reproductively active mated snails, using tannic acid staining and autoradiography after injection of L3Hlleucine. The DB cells of the mated snails appear synthetically active, containing sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The DB are located on the dorsal surface of the cerebral commissure and are known to regulate vitellogenesis and growth and differentiation of female accessory glands. The CDC are two clusters of cerebral neurosecretory cells close to the DB and are known to produce egg-laying hormone (Joosse and Geraerts 1983;Ebberink et al 1985;Schollen and Saleuddin 1986;Saleuddin 1985, 1987;Saleuddin et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The DB are located on the dorsal surface of the cerebral commissure and are known to regulate vitellogenesis and growth and differentiation of female accessory glands. The CDC are two clusters of cerebral neurosecretory cells close to the DB and are known to produce egg-laying hormone (Joosse and Geraerts 1983;Ebberink et al 1985;Schollen and Saleuddin 1986;Saleuddin 1985, 1987;Saleuddin et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics have also been observed in the DB cells of other pulmonate molluscs (Nolte, 1983;Griffond and Vincent, 1985;Saleuddin et al, 1989;Buma et al, 1984;Mounzih et al, 1988). The DB of Lymnaea stagnalis does not abundantly express a peptidergic gene, but they express a gene encoding a P450 analogue, which might suggest steroid synthesis (Teunissen et al, 1992).…”
Section: Discussionmentioning
confidence: 65%
“…The DB cells have general features in common to steroid-secreting gland cells, such as the presence of a large number of mitochondria with longitudinal cristae, abundant lipid droplets and developed SER cisternae. These characteristics have also been described for Helix pomatia (Nolte et al, 1986), Helix aspersa (Wijdenes et al, 1983), Achatina fulica , Theba pisana (Nolte, 1983), Arion rufus (Ezzughayyar and Wattez, 1989), and for the aquatic pulmonates Helisoma duryi (Saleuddin et al, 1989) and Siphonaria pectinata (Saleuddin et al, 1997). Indeed, it was demonstrated that the DB cells of H. pomatia and Lymnaea stagnalis have the capacity to synthesise ecdysteroids (Krusch et al, 1979;Nolte et al, 1986, Mukai andSaleuddin, 1992;Mukai et al, 2001), specifically ecdysone (Nolte et al, 1986).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The dorsal body hormone (DBH), whose origin and chemical nature (peptide and/or steroids) remain to be determinate as they could be different depending on the considered species (Nolte et al 1986;Joosse 1988;Saleuddin et al 1989;Teunissen et al 1992;Garcia et al 1995), is produced from the early juvenile stages (Roubos et al 1988). It regulates cell differentiation of the female accessory sexual organs, the vitellogenesislike process and oocyte maturation, and the synthesis…”
Section: Sexual Polymorphismmentioning
confidence: 99%